Loser in Fight but Winner in Love: How Does Inter-Male Competition Determine the Pattern and Outcome of Courtship in Cricket Gryllus bimaculatus? - Vedenina, Varvara Yu.; Shestakov, Lev S. (Frontiers in Ecology and Evolution, 2018)
Animal females are generally assumed to prefer males that tend to win fights (dominant males). However, a growing number of studies in numerous animal taxa demonstrate no correlation between the male fighting ability and their attractiveness, or even female preferences for fight losers (subordinate males). One of the methods to measure female preferences implies using no-choice tests that evaluate a female’s latency to mating when placed with a single male. Considering that courtship behavior generally contains multimodal signaling, we analyzed 19 behavioral elements demonstrated by both sexes of cricket Gryllus bimaculatus during courtship. To estimate the male dominance status, the males were preliminarily tested in two rounds of fights. The females were shown to mount equally often dominant and subordinate males, but the latencies from the start of antennal contact to mount appeared to be shorter in subordinate than dominant males. During courtship, dominant males demonstrated one of the elements of agonistic display, rocking the body, more frequently and longer than subordinate males. This element was negatively correlated with singing in fight winners but was positively correlated with singing a courtship song in fight losers. Rocking is suggested thereby to function as multiple messages. The song parameters were poorly related with male mating success. The dominant males, rather than subordinate males, tended to produce a higher number of calling chirps, which could be explained by inability of dominant males to quickly shift from aggression to courtship behavior. The results obtained suggest that an increased aggression is likely to interfere with subsequent courtship.